Nowcasting Mexico’s quarterly GDP using factor models and bridge equations - Gálvez-Soriano, Oscar de J. (Estudios Económicos de El Colegio de México, 2020)
I evaluate ﬁve nowcasting models that I used to forecast Mexico’s quarterly GDP in the short run: a dynamic factor model (DFM), two bridge equation (BE) models and two models based on principal components analysis (PCA). The results indicate that the average of the two BE forecastsis statistically better than the rest of the models under consideration, according to the Diebold-Mariano accuracy test. Using real-time information, I show that the average of the BE models is also more accurate than the median of the forecasts provided by the analysts surveyed by Bloomberg, the median of the experts who answer Banco de México’s Survey of Professional Forecasters and the rapid GDP estimate released by INEGI.